An Omnidirectional Stereo Vision-Based Smart Wheelchair. (25th June 2007) - Satoh, Yutaka; Sakaue, Katsuhiko
Abstract : To support safe self-movement of the disabled and the aged, we developed an electric wheelchair that realizes the functions of detecting both the potential hazards in a moving environment and the postures and gestures of a user by equipping an electric wheelchair with the stereo omnidirectional system (SOS), which is capable of acquiring omnidirectional color image sequences and range data simultaneously in real time. The first half of this paper introduces the SOS and the basic technology behind it. To use the multicamera system SOS on an electric wheelchair, we developed an image synthesizing method of high speed and high quality and the method of recovering SOS attitude changes by using attitude sensors is also introduced. This method allows the SOS to be used without being affected by the mounting attitude of the SOS. The second half of this paper introduces the prototype electric wheelchair actually manufactured and experiments conducted using the prototype. The usability of the electric wheelchair is also discussed.